OPINI MASYARAKAT TERHADAP PANTAI PANJANG BENGKULU SEBAGAI TUJUAN PARIWISATA INTERNASIONAL - Linda Astuti (Professional: Jurnal Komunikasi dan Administrasi Publik, 2017)
Pantai Panjang is one of the best tourism objects of Bengkulu. In the 2007, the government had made the tourism as the foremost sector to enhance the development of Bengkulu Province. Governmental programs to make Bengkulu as one of the tourism destination and PantaiPanjang as International tourism object is one of the governmental policy to vary the public opinion. There are people who accept and the other people who refuse the policy. The main informan of this research is people and seller who selling goods in Pantai Panjang. Pantai Panjang as International tourism destination is supported by society because it will increase the income but also the development of another sectors still will be prioritized. Keywords : Public Opinion, Pantai Panjang, International Tourism